Two SAPP2 gene homologs are present in Candida parapsilosis genome - Dostál, Jiří; Merkerová, Michaela; Vinterová, Zuzana; Pichová, Iva; Hrušková-Heidingsfeldová, Olga (Folia microbiologica, 2015)
Candida parapsilosis produces secreted aspartic proteinases (Saps), which contribute to the virulence of this opportunistic pathogen. Gene family containing as many as 14 sequences potentially encoding secreted aspartic proteinases was identified in C. parapsilosis genome. Of them, SAPP1 and SAPP2 genes have been extensively characterized, but only now do we report that two SAPP2 homologs sharing 91.5 % identity occur in C. parapsilosis genome. Existence of SAPP2 homologs points to unexpected complexity of the SAPP gene family.
Keywords: Aspartic Acid Proteases; Molecular Sequence Data; sekvence aminokyselin; Fungal Proteins; molekulární sekvence - údaje; fungální proteiny; Amino Acid Sequence; sekvenční seřazení; Genome, Fungal; Sequence Alignment; aspartátové proteasy; genom fungální; Candida